Patient Perspectives on Patronage of Traditional Bone Setting: A Systematic Review - Sarah Elizabeth Flynn; Sumner Rajaratnam; Colin Kruse; Daniel K. Kisitu; Bradley A. Petrisor (Annals of Global Health, 2026)
Introduction: Traditional bone setters (TBS) treat orthopedic injuries using natural remedies and traditional medicine. These practices can result in complications, including malunion, non‑union, or gangrenous extremities. Despite these complications, communities in low‑ and middle‑income countries trust and rely on TBS for musculoskeletal injuries and pathologies. Understanding patients’ motives for patronizing TBS is necessary to work with TBS to reduce complications. Objectives: The objectives of this study were to assess the reasons patients patronize TBS, identify demographic trends associated with TBS usage, and evaluate how patient perspectives inform an understanding of TBS patronage. Methods: Four electronic databases, MEDLINE and Embase (via Ovid), Web of Science, and the Cochrane Central Register of Controlled Trials (CENTRAL), were searched prior to April 2025. Primary studies examining reasons and patient perspectives on visiting TBS were included. Studies not reporting patient perspectives regarding TBS use were excluded. Study quality was assessed using the Joanna Briggs Institute critical appraisal tools. A narrative synthesis was conducted, with pooled descriptive statistics where appropriate. Results: A total of 28 studies involving 8,147 participants were included. A total of 5 articles directly included patients’ perspectives, while 24 articles reported themes among reasons for the patronage of TBS. The main reasons cited for patronizing TBS were the belief in TBS and affordability. Recommendations from family/friends and negative perspectives on allopathic medicine were both frequently cited. No consistent association between participant demographics and TBS patronage was identified. Conclusions/Discussion: The reasons for patronizing TBS are multifaceted, extending beyond pure affordability and accessibility. The analysis showed that the general preference for TBS over allopathic practitioners and the belief in TBS practices are strongly rooted in the individuals and communities that TBS serve. Despite differing recommendations, collaboration with TBS to improve access to care and reduce complication rates was identified as a future direction.